Thermochemical Conversion of Sugarcane Bagasse: A Comprehensive Analysis of Ignition and Burnout Temperatures - Morais, Leandro C. de [UNESP]; Maia, Amanda A. [UNESP]; Resende, Pedro R.; Rosa, André H. [UNESP]; Nunes, Leonel J. R. (MDPI, 2022)
The Brazilian sugarcane industry generates a significant amount of waste each year, which should be properly analyzed and studied to allow an adequate recovery and application supported by the best understanding of its properties. The present work reports the ignition and burnout temperatures of sugarcane bagasse (SCB) obtained after performing a thermal analysis using four different heating rates. The intersection method (IM) and deviation method (DM) were employed to approach the ignition and burnout temperatures of the sugarcane bagasse. The ignition temperatures of the SCB measured from IM are between 250 and 263 °C, and their burnout temperatures are between 357 and 377 °C. The ignition temperature was in the range of 205 °C to 236 °C for the DM. IM is recommended for determining the ignition and burnout temperatures. In TGA, the heating rates in the range of 10 °C·min−1 and 15 °C·min−1 are suggested due to their accuracy and the contribution to timesaving in the analysis.
Keywords: burnout temperature; combustion; ignition temperature; pyrolysis; sugarcane bagasse; thermal analysis